Low Awareness of Mycoplasma genitalium in Men Who Have Sex With Men in Sydney, Australia. Issue 12 (December 2021) - Varma, Rick; Bradley, Isabella; Patel, Prital; McNulty, Anna
Abstract : Objectives: Mycoplasma genitalium ( M. genitalium ) is a sexually transmitted infection of importance because of the high prevalence rates and antimicrobial resistance (AMR) among men who have sex with men (MSM). Methods: A prospective cross-sectional analysis was carried out on MSM who presented rectally asymptomatic at a central Sydney sexual health clinic or a community site for routine testing. Between March and May 2017, participants were asked to complete a questionnaire before testing. We used multivariable logistic regression to identify factors associated with awareness and concern toward M. genitalium and AMR. Results: Overall, 692 (92.5%) of 746 (95% confidence interval [CI], 90.7–94.5) MSM had no prior awareness of M. genitalium ; 512 (68.6%) of 746 (95% CI, 65.2–72.0) were not concerned or were neutral about the infection; and 234 (31.4%) of 746 (95% CI, 28.0–34.8) were a little, somewhat, or very concerned. High partner numbers (adjusted odds ratio [AOR], 4.2; 95% CI, 2.1–8.2) and inconsistent condom users (AOR, 3.1; 95% CI, 1.2–8.2) and no condoms used (AOR, 3.9; 95% CI, 1.2–12.6) were associated with awareness of the infection. Time since arrival in Australia of more than 10 years (AOR, 1.73; 95% CI, 1.09–2.75), more than 12 months (AOR, 1.91; 95% CI, 1.31–2.79), and recreational drug use (AOR, 1.95; 95% CI, 1.17–3.24) were associated with concern around having M. genitalium . Overall, 61.6% (458/744; 95% CI, 58.2–65.3) MSM reported that they would increase condom use (38.6% agreed and 23.1% strongly agreed) after reading about AMR. Among the remaining 38.4% (286/744), 28.4% indicated a neutral response to increasing their condom use. Relative to MSM born in Australia, Latin American (AOR, 7.3; 95% CI, 2.9–18.4) or Asian MSM (AOR, 2.3; 95% CI, 1.4–3.3), were significantly more likely to increase condom use after reading a statement on AMR. Conclusions: Knowledge of M. genitalium remains low among MSM. Targeted messages using AMR and treatment difficulties with M. genitalium is unlikely to change behavior for a large proportion of MSM. Abstract : Mycoplasma genitalium is affected by antimicrobial resistance. Knowledge remains low, targeted messages using antimicrobial resistance and treatment difficulties are unlikely to change behavior for a large proportion of men who have sex with men.Supplemental digital content is available in the text.